APPLICATION OF LASER FIBER OPTIC FOR BLOOD VELOCITY MEASURMENT - . Dawood, Munqith S; Al-Dergazly, Anwaar A.; Jaafer, Sumia H. (Nahrain University College of Engineering Journal, 2009)
The aim of this paper is to study the possibility of using laser technique for blood flow velocity measurement using the fiber optics to deliver the laser light and receive the scattered light from the blood flowing in different types of vessels. The measuring technique is based on utilizing the Doppler effect in light by using a He-Ne laser source. The correlation function has been used to consider the scattering light from different erythrocytes. Different angles oftransmitted laser inside the vessel were used. It was found that the best angle for all vessels is 45 degrees between the light direction and the direction of blood flow.